PENGARUH MODEL PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING, ART, DAN MATHEMATICS BERBASIS PROJECT BASED LEARNING TERHADAP HASIL BELAJAR AKUNTANSI - Lilis Lilis; Neta Dian Lestari; Chandra Kurniawan (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
The low learning outcomes of students in accounting subjects require educators to change the learning model. This study aims to examine whether or not there is an influence of the PJbL-based STEAM learning model on accounting learning outcomes at SMK Bina Jaya Palembang. This research is anexperimental research with Posttest Only Control Design. Data collection techniques include observation, tests, and documentation. Based on the results of the research that the authors have conveyed, it can be seen the results of the hypotheses that have been made, which are as follows: Tcount > Ttable, or 3.164 > 1.65882, which indicates that Ho is rejected. This means that there is a significant influence between learning outcomes at Vocational High School Bina Jaya Palembang with a project-based learning approach in learning science, technology, engineering, art, and mathematics.